The relationship between personality traits and management styles at ZIMRA Harare. - Mandiyamba, Sharon (Midlands State University, 2017)
The present study sought to examine the relationship between personality traits and management styles. Hundred (100) managers took part in the study and these were drawn from Zimra Harare using simple random sampling. The paper was presented in a bid to clarify the exact relationship between one’s personality traits and the management styles that he/she employs in managing his/her subordinate. The basic assumption was that personality traits determine the management style that managers employ. Quantitative method was used in this study. Personality traits were assessed using the Myers-Briggs Type Indicator Questionnaire and management styles were assessed using the Steve Reybould Management Style Questionnaire. A Pearson’s correlation was employed in testing the personality trait-management style association. The results showed a positive significant correlation between personality traits and management styles (r =0.719). Limitations of the study were presented which other future researches could try to address, these include failure to address the issue of the effect social desirability bias, the generalizability of results and the failure utilise a number of samples drawn nationwide.